2014
DOI: 10.1016/j.ypmed.2014.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood-level socioeconomic deprivation predicts weight gain in a multi-ethnic population: Longitudinal data from the Dallas Heart Study

Abstract: Objective To examine relationship between neighborhood-level socioeconomic deprivation and weight change in a multi-ethnic cohort from Dallas County, Texas and whether behavioral/psychosocial factors attenuate the relationship. Methods Non-movers (those in the same neighborhood throughout the study period) aged 18–65 (N=939) in Dallas Heart Study (DHS) underwent weight measurements between 2000–2009 (median 7-year follow-up). Geocoded home addresses defined block groups; a neighborhood deprivation index (NDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 43 publications
3
67
0
Order By: Relevance
“…These findings are consistent with longitudinal analyses comparing weight gain among non-movers in the DHS, which linked greater duration of residence in higher-NDI neighborhood to a greater likelihood of weight gain. 17 Changes in biomarkers, including cortisol and c-reactive protein, associated with living in disadvantaged neighborhoods suggest that sympathetic activation or alterations to the typical hypothalamic-pituitary-adrenal axis may contribute to a biological pathway by which exposure to neighborhood deprivation promotes weight gain. 27,28 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with longitudinal analyses comparing weight gain among non-movers in the DHS, which linked greater duration of residence in higher-NDI neighborhood to a greater likelihood of weight gain. 17 Changes in biomarkers, including cortisol and c-reactive protein, associated with living in disadvantaged neighborhoods suggest that sympathetic activation or alterations to the typical hypothalamic-pituitary-adrenal axis may contribute to a biological pathway by which exposure to neighborhood deprivation promotes weight gain. 27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Detailed data collection methods from study entry and follow-up have been previously reported. 16,17 At study entry and follow-up, 3,072 participants completed a detailed survey, anthropometric measures, and laboratory testing. The DHS protocol was approved by University of Texas Southwestern Medical Center’s IRB, and written informed consent was obtained from participants at study entry and follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to diverse cross-sectional analyses, more and more longitudinal analyses (Ewing et al 2006, Powell-Wiley et al 2014), analyses examining respondents who move (Hirsch et al 2014, Knuiman et al 2014), and studies of natural experiments (Fitzhugh et al 2010) are appearing in the health sector. Such studies can strengthen the case that environmental modifications can lead to changes in health behaviours.…”
Section: Stronger Experimental Designsmentioning
confidence: 99%